Α Chaotic Map-based Approach to Reduce Black Hole Attacks and Authentication Computational Time in MANETs - Syed, Ahsan Saud Qadri; Atheeq, C.; Ali, Layak; Quasim, Mohammad Tabrez (Engineering, Technology & Applied Science Research, 2024)
The need for Mobile Ad hoc Networks (MANETs) has expanded with the development of mobile computing and wireless sensor network technologies. However, this increase has also led to a rise of the attacks on these networks. In order to ensure high Quality of Service (QoS) and maintain connectivity, MANETs require careful consideration of factors, such as power, connectivity, secure transmissions, authentication, and handovers. Handovers are necessary for seamless network connectivity and require quick authentication to ensure uninterrupted service. Although RSA (Rivest Shamir Adleman) and ECC (Elliptic Curve Cryptography) algorithms are commonly used for authentication due to their fast asymmetric key encryption-decryption and exchange, they are less effective against black hole attacks. Chaos algorithms provide a faster authentication process and are efficient against false behavior black hole attacks. This study demonstrates that the chaos algorithm is a viable option for providing fast authentication and preventing malicious nodes from disrupting the network.